(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Herbal remedies have long been relied upon for the treatment and prevention of illness.Aim: In this study, the antioxidant and antibacterial efficacy of plant extracts used in traditional medicine was evaluated.Materials and Methods: Antibacterial activity was assessed using disc diffusion, while antioxidant power was evaluated using the DPPHradical scavenging assay.Results: Antibacterial activity against Escherichia coli and Staphylococcus aureus and potential antioxidant characteristics were observed in ethanol extracts of Cassia bonducella, Caesalpinia coriaria, Cassia alata, Brownea coccinea, Cassia siamea, Cassia javanica, Amherstia nobilis, and Bauhinia acuminata.Conclusion: Traditional uses of these plants to treat conditions related to pathogenic microorganisms and oxidative stress have been confirmed by their promising antibacterial and antioxidant capabilities, which have been used in a wide variety of herbal medicines. To learn more about the medicinal potential of these plants for human use, more research is needed to identify and isolate their active principles, conduct toxicological tests to ensure their safety, and conduct in vivo experiments on appropriate animals.